2018
DOI: 10.1038/s41598-018-29201-3
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 Transmissions Among Recently Infected Individuals in Southwest China are Predominantly Derived from Circulating Local Strains

Abstract: Although the Guangxi region accounts for 10% of all HIV-1 cases new reported in 2011 in China, the sources of the transmitted HIV-1 strains are virtually unknown. To determine the extent to which recent HIV infections were derived from already circulating local strains as opposed to recently introduced strains, we performed a cross-sectional molecular epidemiological investigation of recent infections across Guangxi during 2012–2013. HIV-1 nucleotide sequences were amplified and sequenced. Phylogenetic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…Using a Bayesian discrete phylogeographic approach to analyze the transmission source of strains among recently infected HIV patients throughout Guangxi in 2012-2013, one study indicated the following subtype/CRF distribution: CRF01_AE (61.1%), CRF07_BC (18.8%), CRF08_BC (16.6%), CRF55_01B (3.1%), and subtype B' (0.4%). Recent research determined that most sequenced transmission strains were derived from already-circulating local strains (93.0%) and that only individuals 18-25 years old were significantly associated with transmission from outside Guangxi [74].…”
Section: Hiv Molecular Epidemiologymentioning
confidence: 99%
“…Using a Bayesian discrete phylogeographic approach to analyze the transmission source of strains among recently infected HIV patients throughout Guangxi in 2012-2013, one study indicated the following subtype/CRF distribution: CRF01_AE (61.1%), CRF07_BC (18.8%), CRF08_BC (16.6%), CRF55_01B (3.1%), and subtype B' (0.4%). Recent research determined that most sequenced transmission strains were derived from already-circulating local strains (93.0%) and that only individuals 18-25 years old were significantly associated with transmission from outside Guangxi [74].…”
Section: Hiv Molecular Epidemiologymentioning
confidence: 99%
“…A study conducted in Guangxi in 2013 targeting newly diagnosed HIV positive cases aged 18 years or older identified four circulating recombinant forms (CRFs) among MSM cases comprising CRF07_BC (44.4%), CRF01_AE (38.9%), CRF55_01B (11.1%) and CRF08_BC (5.6%) 11 . However, in recent years, with the development of modern transportation, especially the establishment of high speed rail, MSM traveling to seek sexual partners outside of their local residence has become more common.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies focused on CRF01_AE featured small participant numbers and short follow-up periods, which necessitates broader comparisons between one genotype and all other genotypes grouped together. Furthermore, only a few studies have focused on the CRF07_BC and CRF08_BC genotypes, which are prevalent in China 12 – 14 . In addition, the effects of CRF01_AE, CRF07_BC, and CRF08_BC have not been directly assessed using mortality as a study end point for either ART-naïve participants or those on ART.…”
Section: Introductionmentioning
confidence: 99%